2023
DOI: 10.1111/pce.14708
|View full text |Cite
|
Sign up to set email alerts
|

TaSINA2B, interacting with TaSINA1D, positively regulates drought tolerance and root growth in wheat (Triticum aestivum L.)

Jianhui Ma,
Yudie Wang,
Xiaoxiao Tang
et al.

Abstract: Wheat (Triticum aestivum L.) is an important food crop mainly grown in arid and semiarid regions worldwide, whose productivity is severely limited by drought stress. Although various E3 ubiquitin (Ub) ligases regulate drought stress, only a few SINA‐type E3 Ub ligases are known to participate in such responses. Herein, we identified and cloned 15 TaSINAs from wheat. The transcription level of TaSINA2B was highly induced by drought, osmotic and abscisic acid treatments. Two‐type promoters of TaSINA2B were found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…According to a classical model, the chaperone-associated E3 ubiquitin ligase CHIP ubiquitinates soluble misfolded proteins associated with chaperone molecules and targets them for degradation through the 26S proteasome during stress [52]. The overexpression of E3 ubiquitin ligases, HSF, HSP, and DnaJ has been demonstrated to enhance root length, chlorophyll content, and antioxidant enzyme activity in transgenic plants, but reduce the production of MDA and ROS under stress [53][54][55][56][57]. In this study, several metabolic pathways were enriched, including "response to misfolded protein", "protein stabilization", "misfolded protein binding", "ubiquitin protein ligase activity", "ubiquitin-like protein ligase activity", "ubiquitin-like protein transferase activity", and "ubiquitin-protein transferase activity" (Figures 4, 5 and S8-S11).…”
Section: Hsfs and Chaperones Collaborated To Maintain The Turnover Of...mentioning
confidence: 99%
“…According to a classical model, the chaperone-associated E3 ubiquitin ligase CHIP ubiquitinates soluble misfolded proteins associated with chaperone molecules and targets them for degradation through the 26S proteasome during stress [52]. The overexpression of E3 ubiquitin ligases, HSF, HSP, and DnaJ has been demonstrated to enhance root length, chlorophyll content, and antioxidant enzyme activity in transgenic plants, but reduce the production of MDA and ROS under stress [53][54][55][56][57]. In this study, several metabolic pathways were enriched, including "response to misfolded protein", "protein stabilization", "misfolded protein binding", "ubiquitin protein ligase activity", "ubiquitin-like protein ligase activity", "ubiquitin-like protein transferase activity", and "ubiquitin-protein transferase activity" (Figures 4, 5 and S8-S11).…”
Section: Hsfs and Chaperones Collaborated To Maintain The Turnover Of...mentioning
confidence: 99%
“…Multiple studies have also indicated that genes controlling wheat root development can enhance its resistance to abiotic stress. For example, TaSINA2B [25] and TaOPRIII [18] enhance drought resistance by regulating the root length and lateral root development; TaANR1 and TaMAD25 enhance wheat nitrogen uptake and drought resistance by increasing the primary root length [26]; and TaSWN enhances wheat adaptation to lownitrogen environments by promoting root development [27]. In our previous study, we cloned several root development-related genes with a genome-wide association study (GWAS), including TaFMO1-5B, which regulates the total root length and surface area [28]; the "Green Revolution" allele Rht-D1b (reduced height-D1b), which significantly increases wheat root systems [29]; and TaGW2-6B (grain width2-6B), whose mutants show enlarged root systems [30].…”
Section: Introductionmentioning
confidence: 99%